NATURAL DISASTERS, WOMEN'S AND CHILDREN'S HEALTH IN REFUGEE SHELTER: Editorial - Berkat, Satrinawati (Journal of Midwifery and Community Health (JMCH), 2025)
The World Meteorological Organization stated that the last four years (2021–2025) were the hottest period ever recorded in human history. This resulted in extreme heat waves, forest fires, prolonged drought, and flash floods.In late November 2025, natural disasters occurred, including floods and landslides, on the island of Sumatra, Indonesia, specifically in the provinces of Aceh, North Sumatra, and West Sumatra. This disaster began with the formation of tropical cyclone Senyar in the Indian Ocean. This tropical cyclone caused prolonged heavy rains, which resulted in flash floods and landslides.